If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(y + -6x) = 12 Reorder the terms: 2(-6x + y) = 12 (-6x * 2 + y * 2) = 12 (-12x + 2y) = 12 Solving -12x + 2y = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. -12x + 2y + -2y = 12 + -2y Combine like terms: 2y + -2y = 0 -12x + 0 = 12 + -2y -12x = 12 + -2y Divide each side by '-12'. x = -1 + 0.1666666667y Simplifying x = -1 + 0.1666666667y
| 6=n+24-8 | | 5-1/4y=10x | | (11x^8/8q^6)*(64q^8/121x) | | 7.5-y=43/4 | | 0=x^2-13x-30 | | 2r+16=1r-25 | | -6(r+7)=-90 | | 20=y-8.1 | | 2x-250=100 | | 9.16515139= | | 5a/5 | | 40+14d=2(-4d-13) | | 8.1+4=20 | | 2x+250=1000 | | 92+78+x=180 | | 49+x+3=90 | | x^2=-1/6 | | 8x-8=10x+7 | | -5x-6y=8 | | 1x+10=7t-14 | | 5(7x-8)=-329 | | 4x^4=324 | | 10000=6x+20 | | 10,000=6x+20 | | 6x+3=92 | | y-4=4(x-1) | | 5+2x=32 | | 3w-6=4.9 | | 3x+6=92 | | 0.28=ln(y) | | 72+x+4=180 | | 3a+2-6+5a= |